Commemorative plaque, Ardeshir Dadysett Pyaav - Ghosh, Ayan (2023)
Scholars believe that Ardeshir Dadysett had commissioned two pyaavs in 1912, one placed at the Dadysett Atash Behram at Marine Lines and another at Dadysett Wadi in Walkeshwar, as corroborated by the information gathered from contemporary newspaper Parsee Prakash. At some later stage, as they fell out of use, the pyaavs were relocated to Jijamata Udyan, where they stand now.